The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/mits.2018.2842020
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measurement Evaluation Framework and Co-Benefit\/Tradeoff Analysis for Connected and Automated Vehicles (CAV) Applications: A Survey

Abstract: A number of Connected and/or Automated Vehicle (CAV) applications have recently been designed to improve the performance of our transportation system. Safety, mobility and environmental sustainability are three cornerstone performance metrics when evaluating the benefits of CAV applications. These metrics can be quantified by various measures of effectiveness (MOEs). Most of the existing CAV research assesses the benefits of CAV applications on only one (e.g., safety) or two (e.g., mobility and environment) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The cooperative automation of CAVs can introduce benefits to current transportation systems with respect to safety, mobility, and environmental sustainability [21]. As one of its major tasks, cooperative longitudinal motion control of multiple vehicles has been widely studied.…”
Section: Cooperative Longitudinal Motion Control Applicationsmentioning
confidence: 99%
“…The cooperative automation of CAVs can introduce benefits to current transportation systems with respect to safety, mobility, and environmental sustainability [21]. As one of its major tasks, cooperative longitudinal motion control of multiple vehicles has been widely studied.…”
Section: Cooperative Longitudinal Motion Control Applicationsmentioning
confidence: 99%
“…Examples of this potential include but not limited to: development of weatherresponsive variable speed limit (VSL) algorithms (Hammit et al, 2017), real-time identification of traffic operation status (Fountoulakis et al, 2017), and identification of high-risk locations (Xie et al, 2019). Nevertheless, in reality there is a trade-off between mobility and safety benefits (Tian et al, 2018), such as a lower VSL tends to reduce the risk of traffic crash, while it will also bring a longer delay. This further emphasized the significance of using microsimulation modeling for performance assessment, since the market penetration rate of CV should be large enough to ensure that sufficient data will be collected to support for the decision-making process for transportation operators at the transportation management center.…”
Section: Discussionmentioning
confidence: 99%
“…System performance with CV penetration rates from 0 to 30 percent were evaluated; results indicated that significant reductions in total delays when CVs reached a penetration rate of 30 percent. Tian et al (2018) provided an in-depth survey on the performance measurement evaluation of CAV applications. This research summarized three typical performance measures: mobility, safety, and environmental benefits, and analyzed the potential tradeoffs and co-benefits of the three performance measures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much literature has focused on the active safety evaluation to study the CACC/ACC rear-end crash risk. Some risk prediction and evaluation models, such as references [11][12][13][14] were proposed, applying macroscopic traffic flow data including density, volume, etc., to proactively perceive potential risk. For example, reference [15] attempted to utilize different driver assistance systems to better reduce small-scale inclement weather-caused rear-end crashes.…”
Section: Introductionmentioning
confidence: 99%